2011
DOI: 10.5021/ad.2011.23.s3.s368
|View full text |Cite
|
Sign up to set email alerts
|

Acute Localized Exanthematous Pustulosis on the Face

Abstract: Acute localized exanthematous pustulosis (ALEP) is a localized variant of acute generalized exanthematous pustulosis, which is characterized by the eruption of multiple scattered pustules following drug administration. A 26-year-old woman presented with multiple erythematous pustules on her face, which had appeared three days after taking antibiotics. Histopathological findings showed subcorneal pustules and mixed inflammatory cell infiltration in the dermis. The pustules were resolved within 2 weeks after the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…Acute generalized exanthematous pustulosis eruptions typically start on the face and flexural folds and extend to the trunk and limbs . Localized AGEP has been reported over a mid‐sternal scar and on the face, cheeks and lips . Diltiazem has also been reported to induce AGEP limited to the distal limbs with sparing of the trunk and flexural folds .…”
Section: Introductionmentioning
confidence: 99%
“…Acute generalized exanthematous pustulosis eruptions typically start on the face and flexural folds and extend to the trunk and limbs . Localized AGEP has been reported over a mid‐sternal scar and on the face, cheeks and lips . Diltiazem has also been reported to induce AGEP limited to the distal limbs with sparing of the trunk and flexural folds .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in patients with AGEP have revealed a high rate of positive patch test responses and in vitro, lymphocyte-proliferative responses compared with other drug eruptions, suggesting that the reaction occurs due to a drug-specific, T-cell-mediated process [25]. All of our patients, though, presented negative patch tests to formaldehyde.…”
Section: Discussionmentioning
confidence: 54%
“…We do not know the reason why there was no lesion on the left upper chest of the patient. Though localized cases of AGEP have been reported mostly on the face, to date there is no case report such as ours with sparing of a localized part of the body . We do not know the exact mechanism, but the sparing of the left upper chest might be related to the sternotomia scar as there are no lesions beyond that area.…”
mentioning
confidence: 66%